Antimicrobial Susceptibility Profiles of Prevotella Species Determined by Gradient Test Method in Two Centers in Istanbul - (:unkn) unknown (ANKARA MICROBIOLOGY SOC, 2020)
Prevotella species, being members of the human microbiota, are obligate anaerobic gram-negative bacteria. These organisms may cause opportunistic infections, including specific oral infections, local or systemic infections. A significant increase of resistance to some antimicrobials has been detected among Prevotella species. The frequency of resistance vary among isolates from different infection sources and between geographic locations. The knowledge about the antimicrobial susceptibility patterns of different Prevotella species is limited in Turkey. Providing the antimicrobial susceptibility data of these bacteria is very important for effective empirical treatment. In this study, we aimed to determine susceptibility data for 12 antimicrobial agents against Prevotella strains originating from human infections, collected in two centers in Turkey. A total of 118 Prevotella strains, isolated from different clinical samples in Marmara University Faculty of Medicine Medical Microbiology and Istanbul University Faculty of Dentistry Oral Microbiology Laboratories between January 2014-December 2017, were tested. Organisms were identified by using MALDI-TOF MS and by 16S rRNA gene sequencing. Minimal inhibitor concentrations of ampicillin, ampicillin-sulbactam, piperacillin-tazobactam, cefoxitin, meropenem, imipenem, clindamycin, tetracycline, tigecycline, moxifloxacin and metronidazole were determined using gradiyent test methodology (E-test; bioMerieux, France) and the European Committee on Antimicrobial Susceptibility Testing, Clinical and Laboratory Standards Institute and Food and Drug Administration guidelines were used for interpretation. Thirteen different Prevotella species were identified, Prevotella bivia and Prevotella nigrescens were the most prevalent species (n=21) followed by Prevotella buccae (n=19). All Prevotella strains were susceptible to piperacillin-tazobactam, cefoxitin, meropenem, imipenem and tigecycline. A total of 2 (1.7%) isolates were resistant to metronidazole and 1 (0.8%) isolate was intermediately resistant to ampicillin/sulbactam. The frequency of resistant isolates against ampicillin, clindamycin, tetracycline and moxifloxacin were 57.6%, 36.4%, 18% and 16.3%, respectively. In conclusion, piperacillin/tazobactam, cefoxitin, and tigecycline displayed high in vitro activity against Prevotella spp. and they all remained good candidates for empiric therapy. Imipenem and meropenem were also found to be very active, but the usage of carbapenems should be reserved for serious mixed infections, potentially accompanied by other resistant organisms. Intermediate resistance to ampicillin-sulbactam and the resistance against metronidazole emphasized the need of periodic monitoring of their susceptibility patterns. The high rates of non-susceptibility to ampicillin, clindamycin, tetracycline and moxifloxacin indicated that these antimicrobials should not be used for treatment of infections without prior antimicrobial susceptibility testing.
Keywords: Prevotella; antimicrobial susceptibility; gradient test; MALDI-TOF MS; 16S rRNA gene; ANAEROBIC-BACTERIA; ANTIBIOTIC-RESISTANCE; IDENTIFICATION; MOXIFLOXACIN; BACTEROIDES; TRENDS